Impact of Cash Flow and Profit on Stock Returns of IDX-Listed Pharmaceutical Companies - Dewi, Ni Kadek Tarisma; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2025)
This study aimed to provide empirical evidence on the effects of operating cash flow, investment cash flow, funding cash flow, and earnings on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange. A sample of 10 companies was selected using purposive sampling, with data collected through non-participant observation. Multiple linear regression analysis was applied. The findings indicate that investment cash flow and earnings positively affect stock returns, while operating and funding cash flows have a negative impact. These results highlight the relevance of signaling and agency theories in explaining these relationships. Keywords: stock return; operating cash flow; investment cash flow; funding cash flow; profit